Taking the linguistic turn in organizational research: challenges, responses, consequences - Alvesson, Mats; Karreman, Dan (2000)
This article takes the linguistic turn, or turns, in the social sciences as its point of departure and discusses the implications for methodology, empirical research, and field practices in social and organizational studies. Various responses can be identified: grounded fictionalism, giving up the hope of making substantive, empirical claims in terms of research texts capturing social phenomena; data-constructionism, where the ambiguous and constructed nature of empirical material gives space for a more relaxed, freer, and bolder way of interacting with empirical material; and discursivism, in which the researcher concentrates on the details of empirical material that lends itself to representations in the form of language, for example, conversations and texts. The article develops some ideas for a more reflective way of dealing with language issues in empirical social research. It argues for a more discourse-near but not discourse-exclusive approach to organizational research and refers to this as discursive pragmatism. - Reproduced
Keywords: Organization of research; Organizations